Synthesis and Characterization of Some Polymeric Lanthanide(II) Complexes - S. Ghosh, (Ms); Pradhan, B. (Asian Journal of Chemistry, 2010)
A series of polymeric complexes having general formula[Ln2(AA)3L4]n, where Ln = La(III), Ce(III), Pr(III), Nd(III), Sm(III) andGd(III), AA = oxalato, L = pyridine-N-oxide or γ-picoline-N-oxide weresynthesised in non-aqueous medium by suitable synthetic method. Thepolychelates were charactarized on the basis of their elemental analyses,conductance, molecular weight, magnetic moment, infrared and electronicspectral data.